The role of socially inclusive special libraries in agricultural institutions to support regional development - Herwan Junaidi; Pudji Muljono; Yusman Syaukat (Perpustakaan Universitas Gadjah Mada, 2025)
Introduction. Social Inclusion-Based Special Library (PKBIS) is a transformation of library services that places the community as an active subject in utilizing information to improve welfare. This study aims to analyze the role and effectiveness of PKBIS in empowering agricultural communities in two assisted locations, namely the Leuwiliang and Cibungbulang Agricultural Extension Centers (BPP), Bogor Regency. Research Methods. The method used is a qualitative and quantitative survey involving 24 respondents, including service users, BPP managers, and PKBIS assistants. Data analysis. Data were analyzed using the Importance Performance Analysis (IPA) method to identify gaps between expectations and service performance. Results. Shows that no service attribute reaches the maximum level of conformity (100%), with an average conformity of 82.11%. Attributes that require priority improvement are in the aspects of proposal assistance and strengthening farmer institutions. These findings emphasize the importance of strengthening mentoring strategies, preparing literacy materials based on local needs, and increasing the capacity of PKBIS managers. Conclusion. The PKBIS at BPP Leuwiliang and Cibungbulang effectively empowers farming communities through information access and capacity building, although the average service conformity level is only 82.11%. Improvements are needed in proposal preparation assistance and strengthening farmer institutions to optimize the potential of PKBIS as a driver of regional development.